Primary advanced non-Hodgkin’s lymphoma of bladder with bilateral hydroureteronephrosis: A case report - Aditya MG; Raisa NS; Pratik A (Journal of Medical and Scientific Research, 2021)
Primary lymphoma of bladder is a very rare entity with a 0.2% incidence of all bladder malignancies. Secondary bladder involvement in malignant lymphoma is more common (10-25%) with preponderance in middle aged females. A non-Hodgkin lymphoma of the bladder can be managed conservatively without surgery and has a better prognosis. Because the presenting symptoms and radiological imaging cannot conclusively rule out a primary bladder lymphoma from other malignant causes, cystoscopy and biopsy with immune-histochemical staining is essential. We present to you a 72-year-old male with complaints of irritative lower urinary tract symptoms and asymptomatic microhematuria. On evaluation computerized tomography (CT) was s/o a large bladder wall mass with bilateral mild hydroureteronephrosis and enlarged pelvic lymphnodes. Cystoscopy and biopsy was done and the report came out to be a non-Hodgkins lymphoma. Whole body positron emission tomography (PET) scan was done which confirmed it to be a primary bladder NHL. Patient was treated with chemotherapy and is now doing well on follow up. We would like to share our experience in managing this case.